The intersectional challenges faced by women of colour in South Africa (Alternate Horizons, 2024)
Gender oppression speaks to the challenges that women face due to their gender. South African societies have become characterised by the oppression of women by men as women continue to exist on the periphery in our community. This article deploys an argument that women still find themselves facing intersecting challenges of patriarchy, racism, economic exploitation and other related forms of heterosexualist gender oppression.